2012
DOI: 10.7547/1020078
|View full text |Cite
|
Sign up to set email alerts
|

Pseudarthrosis After Percutaneous Distal Osteotomy in Hallux Valgus Surgery

Abstract: Nonunion of the first metatarsal after hallux valgus surgery is a rare complication that often results in significant pain and disability requiring surgical management. We report the case of a 42-year-old woman who developed a pseudarthrosis of the first metatarsal after percutaneous retrocapital distal osteotomy of the first metatarsal for a mild hallux valgus deformity. The operative treatment consisted of debridement of fibrous nonunion with plating followed by application of pulsed electromagnetic fields (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The removal of the exostosis makes it necessary for the axis correction with a lower head translation, which ensures more stability. Moreover, the osteotomy is performed intracapsular and safely regarding bone consolidation[ 44 , 45 ]. The Bosch and SERI techniques needed a greater translation of the head, which is not modular.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of the exostosis makes it necessary for the axis correction with a lower head translation, which ensures more stability. Moreover, the osteotomy is performed intracapsular and safely regarding bone consolidation[ 44 , 45 ]. The Bosch and SERI techniques needed a greater translation of the head, which is not modular.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of PEMFs in the treatment of foot and ankle nonunion have been confirmed by other authors not only in the field of fractures. Martinelli et al [51] reported the case of a 42-year-old woman affected by a nonunion of the first metatarsal bone after percutaneous distal osteotomy for hallux valgus deformity. The patient was surgically treated with debridement of the fibrous nonunion with plating followed by the application of PEMFs, and achieved bone consolidation within 3 months.…”
Section: Nonunionsmentioning
confidence: 99%